Peran Birokrasi Pelaksana Mengatasi Pernikahan Dini di Desa Jatisari Jenggawah - Fahurrizal Hidayat; Kahar Haerah (International Forum of Researchers and Lecturers, 2026)
Early marriage remains a social problem in Jatisari Village, Jenggawah District, Jember Regency. This study aims to determine the role of the village government in addressing early marriage. The study employed a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The informants included the village head, the Religious Affairs Office (KUA), the village midwife, religious leaders, and community leaders. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the village government, along with the KUA, the village midwife, and religious leaders, have conducted outreach, reproductive health education, and marriage administration services as an effort to prevent early marriage. Furthermore, the village government has engaged with the community through discussions and provided guidance regarding the negative impacts of early marriage. However, these efforts have not been optimal due to limited human resources, low public awareness, insufficient outreach, and persistent cultural and economic factors that encourage early marriage. Therefore, improved coordination between institutions and ongoing community education are needed to ensure more effective efforts to prevent early marriage.